Probiotic Lactobacillus Plantarum 299v decreases kynurenine concentration and improves cognitive functions in patients with major depression: A double-blind, randomized, placebo controlled study. (February 2019) - Rudzki, Leszek; Ostrowska, Lucyna; Pawlak, Dariusz; Małus, Aleksandra; Pawlak, Krystyna; Waszkiewicz, Napoleon; Szulc, Agata
Highlights: There was an improvement in cognitive functions in group of depressed patients receiving L. Plantarum 299v ( LP299v ) compared to the placebo group. There was a significant decrease in kynurenine concentration in the LP299v group compared to the placebo group. There was a significant increase in 3-hydroxykynurenine : kynurenine ratio in the LP299v group compared with the placebo group. Decreased kynurenine concentration could contribute to the improvement of cognitive functions in the LP299v group compared to the placebo group. Abstract: Background: Interactions between the digestive system and the brain functions have become in recent years an important field of psychiatric research. These multidirectional interactions take place in the so called microbiota-gut-brain axis and emerging scientific data indicate to the significant role of microbiota in the modulation of the central nervous system (CNS) including affective and cognitive functions. Objective: An assessment of psychobiotic and immunomodulatory effects of probiotic bacteria Lactobacillus Plantarum 299v (LP299v) by measuring affective, cognitive functions and biochemical parameters in patients with MDD undergoing treatment with selective serotonin reuptake inhibitors (SSRI). Design: Seventy nine patients with MDD were randomized and allocated to a double-blind, placebo-controlled trial. Participants received either a SSRI with the probiotic LP299v (n = 40) for a period of 8 weeks or a SSRI with the placebo of the probiotic (n = 39) for the same period. The severity of psychiatric symptoms was assessed using Hamilton Depression Rating Scale (HAM-D 17), Symptom Checklist (SCL-90) and Perceived Stress Scale (PSS-10). Cognitive functions were assessed using the Attention and Perceptivity Test (APT), Stroop Test parts A and B, Ruff Figural Fluency Test (RFFT), Trail Making Test (TMT) Parts A and B and the California Verbal Learning Test (CVLT). Biochemical parameters such as tryptophan (TRP), kynurenine (KYN), kynurenic acid (KYNA), 3-hydroxykynurenine (3HKYN), anthranilic acid (AA), 3-hydroxy anthranilic acid (3HAA), tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), interleukin 1-beta (IL-1b) and cortisol plasma concentrations were measured. Results: Sixty participants finished the study and were analyzed: 30 participants in the LP299v group and 30 participants in the placebo group. There was an improvement in APT and in CVLT total recall of trials 1–5 in the LP299v group compared with the placebo between baseline and after 8 weeks of intervention. There was a significant decrease in KYN concentration in the LP299v group compared to the placebo group. We also observed significant increase in 3HKYN:KYN ratio in the LP299v group compared with the placebo group. Additionally, Repeated Measures ANOVA revealed a significant effect of interaction of Treatment x time for AA concentration. However, results of post hoc analysis did not reach statistical significance in neither probiotic nor placebo group. There were no significant changes of TNF-α, IL-6 and IL-1b and cortisol concentrations in neither probiotic nor placebo groups. Conclusions: Augmentation of SSRI treatment with probiotic bacteria Lactobacillus Plantarum 299v improved cognitive performance and decreased KYN concentration in MDD patients. Decreased KYN concentration could contribute to the improvement of cognitive functions in the LP299v group compared to the placebo group. To our knowledge results of this study are the first evidence of improvement of cognitive functions in MDD patients due to probiotic bacteria and this is the first evidence of decreased KYN concentration in MDD patients due to probiotic bacteria.